Evaluating the Effect of Outpatient Registration Systems on Patient Recommendations Using Value Stream Mapping and Path Analysis - Malik Qilsi, Fatkhur Ruli; Bukhori, Saiful; Firman, Firman (Journal of Agromedicine and Medical Sciences, 2025)
Digital transformation in healthcare requires hospitals to adopt efficient and integrated information systems. This research aims to analyze the influence of outpatient registration information system types—conventional, Hospital Management Information System (HMIS), and Mobile JKN—on recommendations to others using Value Stream Mapping (VSM) and path analysis with SmartPLS. The study was conducted at Citra Husada Hospital Jember with 98 respondents selected through convenience sampling. The VSM results indicate that Mobile JKN has the shortest total service time (1 hour 32 minutes) and the highest efficiency value (8.6%). Statistical analysis shows that interaction with medical personnel, ease of access, ease of use, and data security significantly influence patient satisfaction. Medical information satisfaction and overall service quality are proven to be the main factors driving patient recommendations. Consequently, Mobile JKN is the most efficient registration system alternative and has the potential to improve hospital service quality. Optimization of system integration and user education is recommended to support digital-based healthcare service transformation.